Rancangan dan Refleksi Strategi Pengembangan dan Evaluasi Kinerja dalam Organisasi Pendidikan Islam - Surahman; Sulhan, Ahmad (PT. Cahya Edupreneur Indonesia, 2025)
This research aims to design and reflect on development strategies and performance evaluation in Islamic education organizations at Kending Sampi primary school in Pandan village. Using a narrative qualitative method, this research explores the experiences, views and practices of educators, students and parents regarding the implementation of educational strategies in schools. Information was obtained through in-depth interviews, focus group discussions and observations. The findings show that the school is able to integrate Islamic principles into the curriculum and teaching methods, creating a supportive atmosphere. Teachers actively participate in training to improve their skills, while parental involvement is very positive. While varied ways of learning can boost student morale, the performance evaluation process should remain standardized. This study offers insights for continued progress at Kending Sampi primary school and other Islamic education institutions.